KOMPOSISI BOTANI PADA PERKEBUNAN KELAPA SAWIT MILIK PT. NUSA INA GROUP DI KECAMATAN SERAM UTARA TIMUR KOBI KABUPATEN MALUKU TENGAH - Eoh, Marna (Program Studi Pendidikan Biologi FKIP Unpatti, 2023)
Background: This study aims to determine the botanical composition of pastures, in the oil palm plantation of PT. Nusa Ina Group in East Kobi North Seram District. Methods: This study used a survey method through direct observation and measurement of forage in the oil palm plantation area. Results: The results of this study indicate that the botanical composition of forages found in the oil palm plantation area is 10 species, which are divided into 3 groups, namely grasses 7 species (73.09%), legumes 2 species (18.47%) and weeds 1 species ( 8.44%). Conclusion: Botanical composition of pastures in the oil palm plantation area of ​​PT. Nusa Ina group In North Seram District Kobi based on dry weight was dominated by grass 73.09%, legumes 18.47%. It is necessary to improve the quality of forage in oil palm plantations by adding leguminous species.